Edukasi Inovasi Model Bisnis Berkelanjutan Melalui Pengabdian Masyarakat di PT. Henan Putihrai Asset Management - Liem Bambang Sugiyanto; Velly Anatasia; Denny Timothy; Muhammad Khusaini (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service initiative aimed to develop sustainable business model innovation at PT Henan Putihrai Asset Management (HPAM) using a participatory approach. The program focused on understanding shifts in investor demographics, which are increasingly dominated by Generation Z and Millennials, the importance of digital transformation, and the application of a three-pillar business model innovation framework: value proposition, value creation, and value capture. The methods included socialization sessions, facilitated discussions, and presentations on potential innovation opportunities delivered to HPAM managers. The results indicate increased employee awareness of the importance of business model innovation in response to fintech disruption and rising ESG expectations. This is reflected in the overall event success assessment, measured across objectivity, educational value, accountability, and transparency as rated by participants, with descriptive statistics exceeding 3.8. These findings suggest that collaboration between academic facilitators and industry practitioners can generate and strengthen innovative solutions. The initiative also contributed positively to the development of an innovation culture at HPAM, encouraging adaptation to investor needs that are increasingly personalized and digitally driven. It is expected that HPAM will implement these innovative strategies to enhance competitiveness in the digital era and achieve sustainable growth.